How to use a rotahaler. Issue 1 (January 1986) - Pedersen, S
Abstract : The bronchodilator response after five different modes of salbutamol inhalation by rotahaler was assessed in 15 asthmatic children in a double blind cross over study. Inspiratory flow rates lower than 50 litres/minute were associated with a significant reduction in response compared with flow rates higher than 60 litres/minute, but tilting the head back during inhalation and holding the breath for 10 seconds had no significant effect on bronchodilation. Peak inspiratory flow rates measured in 150 normal children and 13 asthmatic children with acute wheeze showed that many young children and many children with severe bronchoconstriction were unable to generate a sufficiently high inspiratory flow rate to obtain maximum benefit from rotahaler treatment. Children using a rotahaler should be taught to inhale as quickly as possible and not with a quiet deep breath as recommended in the instruction leaflets.